Prospek Pembuatan Pakan Ayam Dari Bahan Baku Lokal (Contoh Kasus Gorontalo) - Akhadiarto, Sindu (Badan Pengkajian dan Penerapan Teknologi, 2015)
Currently chicken feedÃ¢â‚¬â„¢sÃ‚Â price continues to rise, therefore a lot of chicken farmers suffered since the cost spent for feed could reach up to 70% of the total businessÃ¢â‚¬â„¢ cost. Most farmers still depend on the manufactured feed in, which the ingredients are imported.Ã‚Â Due to the increase of feed ingredientsÃ¢â‚¬â„¢Ã‚Â price in the international market (e.g. corn, soy, fish powder), the manufactured feed price also increase. To overcome the high price of manufactured feed, the local society should be equipped with the technology to produce local feed using local ingredients. The feed equipment will be made and adapted to the local conditions. The feed preparation technique is computerized using the feeding program